The Role of Lifestyle Behaviors in Early Childhood Obesity: Insights from Pre-School Populations - Alhussain, Maha H.; Al-mashouf, Wafa Sultan; Albadr, Nawal A.; Almoghirah, Haila A.; Arzoo, Shaista; Alfayez, Farah Fayez; Al-Hazzaa, Hazzaa M. (International Journal of Child Health and Nutrition, 2025)
Aim: Childhood obesity is an escalating global health concern. Identifying modifiable risk factors is crucial to inform effective prevention strategies. This study explored lifestyle behaviors, including chrono-nutrition and sedentary behaviors, associated with overweight/obesity among Saudi pre-school children. Methods: This cross-sectional study of 450 children aged 3-6 years from 20 pre-schools assessed chrono-nutrition, sedentary, and sleep behaviors through questionnaires filled by parents/guardians. Height, weight, and skinfold thickness were measured. BMI was calculated using International Obesity Task Force classifications for children aged 2-18. Results: Overweight/obesity prevalence in preschoolers was 22.67%. Weight, skinfold, and body fat percentage were significantly higher among the overweight/obese group (p<0.001). A significant association (p=0.009) was observed between sleeping time and BMI. However, insignificant associations were observed between BMI and chrono-nutrition or physical activity. Logistic regression analysis revealed that evening (OR=0.142, 95%CI: 0.024-0.834, p=0.031) and irregular screen time (OR=0.162, 95%CI: 0.036-0.730, p=0.018) as well as more than two hours of napping (OR=0.268, 95%CI: 0.073-0.987, p=0.048) were associated with lower odds of overweight or obesity status. Conclusions: Selected lifestyle behaviors exhibited significant associations with lower overweight/obesity among preschoolers. Future studies on pre-school children’s lifestyle behaviors are warranted to enhance preventive health education and health promotion among young children.